Evaluasi Implementasi Aplikasi P-Care dengan Metode Task Technology Fit di Puskesmas Kota Blangkejeren - Rita Yuniarti; Asriwati Asriwati; Miskah Afriani (Jurnal Kesehatan Amanah, 2025)
Advances in information technology in the health sector encourage the use of digital applications to improve service efficiency. One of them is the Primary Care (P-Care) application developed by BPJS Kesehatan to support the implementation of National Health Insurance (JKN) in first-level health facilities. This study aims to evaluate the implementation of P-Care at the Blangkejeren City Treatment Center using the Task Technology Fit (TTF) approach. This study uses a descriptive qualitative method with a narrative approach. Data was collected through in-depth interviews with the heads of health centers, medical personnel, and patients, and analyzed interactively through the stages of reduction, presentation, and drawing conclusions. The results of the study show that the perception of health workers on the ease of use and benefits of P-Care is quite positive, although it is still constrained by system disruptions and infrastructure limitations. Attitudes and interest in use remain high, but actual usage is not fully optimal because there is still a combination of digital and manual processes. The conclusion of this study states that although P-Care has supported service improvement, optimization of application features and infrastructure improvements are urgently needed. Training support and strengthening internal management at health centers are important factors to ensure the sustainability of the implementation of the application as a whole.